ACHIEVING ORGANIZATIONAL PERFORMANCE THROUGH BUSINESS PROCESS OUTSOURCING - Kolawole, Ibukun Olorunisola; Agha, Erezi Ann (European Scientific Journal, ESJ, 2015)
This paper examines in multiple perspectives, the concept of business process outsourcing, issues and effects of outsourcing on organizational performance. It focuses on the benefits, drivers and challenges companies face in outsourcing their non-core activities and how they achieve performance through effective outsourcing. The study found that outsourcing, as it is now known, has been around for many decades and evaluate the factors affecting outsourcing decisions in Nigeria. Outsourcing plays an important role in organizations, helping them ensure competitiveness, competitive advantages, increase efficiency and effectiveness. The study analyzes the role of outsourcing in organizations and concluding that the world has embraced the phenomenon of outsourcing and companies have adopted its principles to help them expand into other markets and gain competitive advantage.